The Effect of Green Project Financing, Investment Sustainability, and Green Bonds Policy on the Growth of Renewable Energy Industry in Indonesia - Loso Judijanto; Rina Destiana; Dwi Dersmi Selan; Budi Sulistiyo Nugroho; M. Ali Mauludin (Westscience Press, 2024)
This study investigates the effect of green project financing, investment sustainability, and green bonds policy on the growth of the renewable energy industry in Indonesia through a quantitative analysis. A cross-sectional survey design is utilized to collect data from stakeholders involved in renewable energy projects, financial institutions, government agencies, and other relevant entities. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) 3 software is employed to analyze the data and examine the relationships between the latent constructs. The findings reveal significant positive relationships between green project financing, investment sustainability, green bonds policy, and the growth of the renewable energy industry. These results underscore the importance of supportive policy frameworks, access to finance, and sustainable investment practices in driving renewable energy deployment. The study contributes to a deeper understanding of the factors influencing renewable energy development in Indonesia and provides valuable insights for policymakers, investors, and practitioners seeking to advance sustainable energy transitions.